2011
DOI: 10.3109/13693786.2010.503196
|View full text |Cite
|
Sign up to set email alerts
|

A case of kerion celsi caused byMicrosporum gypseumin a boy following dermatoplasty for a scalp wound from a road accident

Abstract: We report a rare case of kerion celsi of the scalp caused by Microsporum gypseum in a boy 1 month after he received dermatoplasty for a scalp injury from a road accident. Species identification was performed by observation of morphologic and biochemical characteristics and sequencing of the internal transcribed spacers (ITS) 1 and 2. Treatment with oral terbinafine and topical naftifine-ketoconazole cream after washing the hair with ketoconazole shampoo was effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 6 publications
1
21
1
5
Order By: Relevance
“…2). 23–25 Our results were similar to those in other Tunisian studies, noting that living conditions, large family size and close contact with other infected children at school, physical contact with animals and playing outside may facilitate fungal transmission 8,11,12,26 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2). 23–25 Our results were similar to those in other Tunisian studies, noting that living conditions, large family size and close contact with other infected children at school, physical contact with animals and playing outside may facilitate fungal transmission 8,11,12,26 …”
Section: Discussionsupporting
confidence: 88%
“…The prevalence data we obtained from our study were different with results as reported from many other regions of the world. In Tunisia, the incidence of inflammatory TC is varied from 2.3% to 13% 1,11–16 . This value was lower than that observed in Spain (18.2%) and Saudi Arabia (19.8%) 17 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The same resistance mutation combination has been described also in cystic fibrosis patients, recently [35]. In general, the development of azole resistance in Aspergillus fumigatus in cystic fibrosis patients due to TR34/L98H and other cyp51 A mutations has been published [36][38]. However, this group of patients is different to our severely immunocompromised hematological patients' population, since culture of fungal diagnostic from respiratory samples is mostly positive in cystic fibrosis patients; the amount of DNA is not the limiting factor investigating cyp 51A mutations from isolates.…”
Section: Discussionmentioning
confidence: 66%
“…Примером может служить случай импетиго-подобных высыпаний на лице у 3-летней девочки, вызванный телеоморфой Trichophyton interdigitale, успешно леченный итраконазолом (пероральный прием) с местными аппликациями 1% крема нафти-фина и шампуня с кетоконазолом [21]. Китайские дерматологи применяли нафтифин у месячного ре-бенка при керион Цельса волосистой части головы, вызванного Microsporum gypseum (системно приме-нялся тербинафин) [22].…”
Section: клиническая дерматология и венерология 2 2015unclassified